Impact of Forestry on Regional Economy of East Kalimantan Province, Indonesia - Sudharto, Dwi (1999)
Forestry development in Indonesia has given many advantages to the Indonesian economy. However, some provinces which are rich in forest products are not receiving maximum impact of the sector. Many number of research projects have shown that the presence of this sector was unable to stimulate the growth of downstream industries and has been disadvantageous to regional development. The East Kalimantan has a large area of forest, covering more than 76% of the total land area. This province leads in the forestry activity in Indonesia. In 1997, there were 72 FCRs, 28 plywood mills, 116 sawmills, and 49 other wood industries. This study aims to identify the impact of the forestry sector on the regional economy of East Kalimantan with regards to its GDRP, multipliers, linkages, and regional leakage using 1-0 analysis. This study also analyses several alternative policies and inter-sectoral linkages in the forestry sector. The experimental results indicate that the contribution of forestry in East Kalimantan in 1995 to GORP amounted to 11.70% (rank 3 out of 10 sectors) after Mining and Quarrying (34.10%) and Manufacturing Industry (24.10%). This contribution can be increased further through various government policies. The forestry sector has a high value of multipliers, namely 1.8211 (total output), 1.5388 and 1.8416 (Type I and Type II income multipliers), 1.4196 and 1.5997 (Type I and Type II employment multipliers). Plywood and sawntimber industries are the two forestry activities that have good prospects. This sector has high value of output backward linkage (1.8211), low value of output forward linkage (0.8014), low value of income backward and forward linkage (0.8550 and 0.6494), and low value of employment backward and forward linkage (0.9755 and 0.8529). The level of regional leakage of the forestry sector in this province is high (ranks 4 out of 10 sectors). Plywood and sawntimber have the highest value of regional leakage among all of the forestry activities. To increase the role of the forestry sector in the future, fourteen policy scenarios of exports have been incorporated in this study. The selection of the policy scenarios are dependent on the forest potential in this province. Intersectoral linkage needs to be more developed to obtain value- added. incentives need to be provided to promote the development of integrated woodbased industrial complexes, including ways to overcome constraints and bottlenecks in the input- supplying sector, and development of small and medium scale enterprises (SMES).